PENGARUH DINING SERVICE QUALITY (DINESERV) TERHADAP CUSTOMER SATISFACTION DAN REVISIT INTENTION (Survei pada Pelanggan D’COST Seafood Restaurant Malang Town Square) - Lirizki Agustimas Anwar; Suharyono Suharyono; Aniesa Samira Bafadhal (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
This research was explanatory research and using quantitative approach. The variables of the research were Dining Service Quality (DINESERV), Customer Satisfaction, and Revisit Intention. The population of this research was customer of D’COST Seafood Restaurant branch of Malang Town Square with 18 years old as the minimum age. Questionnaire was used in order to gather the 112 respondents’s data. In addition, descriptive analysis and path analysis were used in order the analyzed data. The results of this research show that Dining Service Quality (DINESERV) has a positive effect on Customer Satisfaction, because it has a probability value (0,000) < 0,05 which means there is a significant influence. Dining Service Quality (DINESERV) has a positive effect on Revisit Intention, because it has a probability value (0,019) < 0,05 which means there is a significant influence. Customer Satisfaction has a positive effect on Revisit Intention, because it has a probability value (0,000) < 0,05 which means there is a significant influence. The results of direct and indirect effect indicates that Customer Satisfaction variable is the intermediate variable that works partially, meaning that the variable of Dining Service Quality (DINESERV) directly have a significant effect to Revisit Intention without going to go through Customer Satisfaction. Keywords: Dining Service Quality, DINESERV, Customer Satisfaction, Revisit Intention АBSTRАK Penelitian ini merupakan penelitian eksplanatori (explanatory research) dengan pendekatan kuantitatif. Variabel pada penelitian ini terdiri dari Dining Service Quality (DINESERV), Customer Satisfaction, dan Revisit Intention. Populasi penelitian ini adalah pelanggan D’COST Seafood Restaurant cabang Malang Town Square yang minimal berusia 18 tahun. Kuesioner digunakan sebagai instrumen pengumpulan data dari 112 sampel penelitian. Teknik analisis yang digunakan adalah analisis deskriptif dan analisis jalur (path analysis). Hasil penelitian ini menunjukkan bahwa Dining Service Quality (DINESERV) berpengaruh positif terhadap Customer Satisfaction, karena memiliki nilai probabilitas (0,000) < 0,05 yang berarti terdapat pengaruh yang signifikan. Dining Service Quality (DINESERV) berpengaruh positif terhadap Revisit Intention, karena memiliki nilai probabilitas (0,019) < 0,05 yang berarti terdapat pengaruh yang signifikan. Customer Satisfaction berpengaruh positif terhadap Revisit Intention, karena memiliki nilai probabilitas (0,000) < 0,05 yang berarti terdapat pengaruh yang signifikan. Hasil pengaruh langsung dan tidak langsung menunjukkan bahwa variabel Customer Satisfaction merupakan variabel antara yang berfungsi secara parsial, artinya variabel Dining Service Quality (DINESERV) secara langsung berpengaruh signifikan terhadap Revisit Intention tanpa harus melalui Customer Satisfaction. Kata Kunci: Dining Service Quality, DINESERV, Customer Satisfaction, Revisit Intention